Delayed Failure of M6-C Cervical Disc Arthroplasty After Conversion of Adjacent Cervical Disc Arthroplasty to Fusion: A Case Report. Issue 2 (18th April 2023) - Clohisy, John C. F.; Abjornson, Celeste; Bauer, Thomas W.; Baral, Elexis; Albert, Todd J.
Abstract : Case: We present a delayed failure of an M6-C cervical disc arthroplasty after conversion of a subjacent failed cervical disc arthroplasty to fusion. The annular component had failed, and the core had been ejected. Histology demonstrated a giant cell reaction to polyethylene debris, and tissue cultures were positive for Cutibacterium acnes . Conclusion: This is the first report of M6-C failure after conversion of an adjacent arthroplasty to fusion. A growing number of reports surrounding the M6-C failure rate and mechanisms raise concern about the device's durability and underscore the importance of routine clinical and radiographic surveillance for these patients.